Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1007/s11664-999-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

Creep deformation behavior in eutectic Sn-Ag solder joints using a novel mapping technique

Abstract: Creep deformation behavior was measured for 60-100 µm thick solder joints. The solder joints investigated consisted of: (a) non-composite solder joints made with eutectic Sn-Ag solder, and (b) composite solder joints with eutectic Sn-Ag solder containing 20 vol.%, 5 µm diameter in-situ Cu 6 Sn 5 intermetallic reinforcements. All creep testing in this study was carried out at room temperature. Qualitative and quantitative assessment of creep deformation was characterized on the solder joints. Creep deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…The intermetallic compounds also help Cu particles to uniformly distribute in the composite solder. The average nearest particles spacing, λ 0 , is estimated from 18 (2) where A is the area measured, and N is the number of Cu particles in the area measured. Based on the statistical measurement, the s average nearestparticles spacings of 5vol.%Cu and 10vol.%Cu particles-enhanced SnPb-based composite solder are 13.1 µm and 6.5 µm, respectively.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The intermetallic compounds also help Cu particles to uniformly distribute in the composite solder. The average nearest particles spacing, λ 0 , is estimated from 18 (2) where A is the area measured, and N is the number of Cu particles in the area measured. Based on the statistical measurement, the s average nearestparticles spacings of 5vol.%Cu and 10vol.%Cu particles-enhanced SnPb-based composite solder are 13.1 µm and 6.5 µm, respectively.…”
Section: Microstructurementioning
confidence: 99%
“…1 Lucas et al 2 compared the creep behavior of the Sn-3.5Ag solder using small, single shear-lap soldered joints with in-situ reinforcements. It is found that the global creep-strain rate was decreased in composite solder joints.…”
Section: Introductionmentioning
confidence: 99%
“…Since eutectic Sn-3.5Ag solder is considered as a leading candidate of Pbbearing solders, several approaches have been used to improve its comprehensive properties such as creep resistance, thermomechanical fatigue resistance, mechanical strength, and solder joint reliability. [15][16][17][18][19][20][21][22][23][24][25][26][27] Among these approaches, the composite approach was designed mainly to improve its service performance, including service temperature capability. Composite solders, whether tested as bulk or as joint specimens, generally showed improved properties.…”
Section: Introductionmentioning
confidence: 99%
“…Creep testing was carried out on these solder joints, marked with a laser pattern or a scratch, 14 using dead-weight loading on a miniature creeptesting frame fixed on an optical microscope. The de formation of the polished side of the solder joint was monitored using a Kodak (Rochester, NY) chargecouple device camera connected to a microscope and a computer.…”
Section: Creep Testmentioning
confidence: 99%